Mother knowledge of lactation massage at PMB Rahmiyati - Rahayu, Linda Putri; Rahmawati, Dwi; Rahman, Subhannur; Dona, Sismeri (Ananda - Health & Education Foundation, 2026)
Background: Exclusive breastfeeding (EBF) is crucial for infant health, yet coverage in Banjarmasin, Indonesia, remains below national targets. Lactation massage is an effective technique to address common breastfeeding problems, but its success may be hindered by inadequate maternal knowledge. Objective: This study aimed to describe the knowledge of postpartum mothers regarding lactation massage at an independent midwifery practice (PMB Rahmiyati) in Banjarmasin. Method: A quantitative descriptive study with a survey approach was conducted. The sample comprised 35 postpartum mothers recruited using total sampling. Data were collected using a validated and reliable questionnaire on lactation massage knowledge, adopted from Putri (2022). Knowledge scores were categorized as good (76-100%), fair (56-75%), or poor (≤55%). Data were analyzed using descriptive statistics (frequency and percentage). Results: The study found that 20 respondents (57.1%) had good knowledge of lactation massage. However, a substantial combined proportion of 42.9% had either fair (20.0%) or poor (22.9%) knowledge. This knowledge gap existed despite the majority of mothers being in the optimal reproductive age (85.7%), having a senior high school education (91.4%), and being unemployed (68.6%). Conclusion: While more than half of the mothers demonstrated good knowledge, a significant portion still lacks adequate understanding of lactation massage. These findings underscore the urgent need for continuous, structured educational interventions by health workers to empower all mothers, particularly in utilizing effective lactation management strategies.